P-172 Characterization of Primary Colonic Stem Cells in a Murine Model of Colitis-Associated Cancer. (March 2016) - Diaz, Sophia; Davies, Julie; Santaolalla, Rebeca; Dheer, Rishu; Lang, Jessica; Phillips, Matthew; Abreu, Maria
Abstract : Background: Connection between chronic inflammation and cancer is well known. Colon cancer is the third most prevalent cancer worldwide, and it is recognized that tumor initiation, growth, invasion, and metastasis are promoted by cancer stem cells (CSCs). Specifically, the chronic inflammation that occurs in ulcerative colitis (UC) patients can lead to colitis-associated cancer (CAC) in 25% of patients, but there is currently no way to predict which patients will develop cancer. Aim: The primary aim of this study was to develop and optimize a platform that immunophenotypes and characterizes the tumorigenic CSCs found in colitis-associated tumors. Methods: C57Bl/6J mice underwent a 56-day model of colitis-associated neoplasia. Mice were given an intraperitoneal injection of azoxymethane (AOM, 14 mg/kg) on day 0. On days 14 and 35, mice were administered a 7-day cycle of 2.5% dextran sodium sulfate (DSS) with 2 weeks of recovery time after each cycle. Mice were sacrificed on day 56. We excised the colonic tumors along with the surrounding, non-dysplastic tissue as a control for each sample, and dissociated them into single cell suspensions. We then performed and optimized the ALDEFLUOR (STEMCELL Technologies), or ALDH-detecting, assay for this cell type. Following the assay, cells were fluorescently stained for EpCAM to isolate intestinal epithelial cells, and for the following putative CSC markers for flow cytometric analysis: CD133, CD166, CD44, and CD49f. Results: CSC populations differed in colitis-associated tumors versus the surrounding non-dysplastic tissue. Specifically, tumor intestinal epithelial cells (EpCAM+ cells) had a higher expression of the putative stem-cell markers, including ALDH and CD49f, compared to control tissue. Conclusions: This study used a novel CSC flow cytometry panel and the AOM-DSS murine model to show that primary colonic CSCs can be successfully isolated to single cell suspensions, immunophenotyped, and quantified. These results in particular suggest that tumors may have a higher stem cell population and/or a greater "stemness" profile when compared to surrounding non-dysplastic tissue. Thus, this panel can be used to potentially sort upon these tumorigenic CSCs and create cell lines from AOM-DSS-derived tumors in different colitis-associated cancer models. Cell lines like these would be instrumental in studying the neoplasia-to-cancer transition in a more specific manner.